Quercetin encapsulated iron oxide nanoparticles with enhanced antioxidant and anticancer activities - Vijayasri, K. (Asian Journal of Pharmaceutics (AJP), 2023)
The purpose of this study was to develop iron oxide nanoparticles loaded with quercetin that could effectively prevent cancer and exhibit antioxidant properties. Co-precipitation was employed to create the nanoparticles, which were subsequently evaluated for particle size, zeta potential, entrapment efficiency, and in vitro drug release. The optimized formulation, F5, was further characterized using techniques such as differential scanning calorimetry and scanning electron microscopy and tested for its anticancer and antioxidant activities, as well as intestinal penetration. The results showed that the addition of cyclodextrin and polyethylene glycol reduced the toxicity of ferrous oxide and improved the solubility of quercetin. The antioxidant activity of quercetin iron oxide nanoparticles was also demonstrated using H2O2 scavenging abilities. Furthermore, the drug permeation studies conducted on goat intestinal tissue showed that the F5 formulation had the highest levels of intestinal permeability, as well as anticancer activity and antioxidant properties, compared to the pure drug. In conclusion, the optimized quercetin iron oxide nanoparticles F5, with their optimal iron oxide, medium beta-cyclodextrin, and high surfactant levels, demonstrated improved drug release, antioxidant activity, and anticancer efficacy, making them a promising candidate for further development as a cancer prevention and treatment agent. The high scientific rigor and advanced methodology utilized in this study support its significance in the field of drug delivery and cancer research.